The Impact of Learning Strategies (Values Clarification Technique and Social Science Inquiry) and Students' Cognitive Style on Tolerance - Pramana, Atan; Sumarno, Alim; Khotimah, Khusnul; Mariono, Andi (Indonesian Journal of Instructional Media and Model, 2023)
Citizenship Education requires learning strategies to be developed, namely Values Clarification Technique (VCT) and social science inquiry. Another factor that has an impact on learning effectiveness is the cognitive style which consists of field dependence (FD) and field independence (FI). The research aims: first, to find out the differences in the acquisition of tolerant values with the application of values clarification learning strategies and social science inquiry; Second, knowing the difference in the value of tolerance for those who have FD and FI; And third, knowing the interaction between the application of learning strategies and cognitive styles in the development of tolerance. Experimental research with a quasi-experimental design. The research subjects were undergraduate level students who were taking Civics courses. Four classes were selected as samples using a cluster sampling, with a total of 149 students who became respondents. Cognitive style test and tolerance test as instruments. Data analysis using MANOVA. Conclusion: first, there is a significant difference in the tolerant attitudes of students between classes that implement VCT and social science inquiry learning activities. The class that applied the VCT strategy got a posttest average tolerance attitude higher than the social science inquiry class; Second, there is no difference in the tolerant attitude of students who have a significant cognitive style; And third, there is interaction between learning strategies and cognitive styles in the development of tolerance. Overall, this research contributes to increasing tolerant attitudes which end at the academic level and attitudes of students. Keywords: learning strategies, cognitive style, tolerance